(untitled) (Research, Society and Development, 2022)
Introduction: Fibroedema Geloid (FEG) refers to a change in the circulatory, connective system, causing low oxygenation in the tissues, resulting in little elasticity and tissue malnutrition. Manual Lymphatic Drainage (MLD) is a treatment method for FEG that uses manual maneuvers, providing stimulation of the lymphatic system to conduct the lymph through capillaries, ducts and lymphatic vessels. Objective: To identify the immediate effect of Manual Lymphatic Drainage on Fibroedema Geloid in young women. Methodology: This is an exploratory, analytical, descriptive research with a cross-sectional design and a quantitative approach. The research was carried out at the Physiotherapy study center with young women enrolled in the 10th semester of the course at a higher education institution. An evaluation was carried out to identify the graduation and the clinical aspect of the Fibroedema Geloid, perimetry was carried out and photographic records were taken. Then, the participants who were part of the established criteria, were submitted to a Manual Lymphatic Drainage session, after the session they were evaluated again. Results: It was possible to perceive a statistically significant improvement in the appearance of the skin, in the graduation of the EGF. There was a reduction in the edema, also improving the perimetry, however, it was not statistically significant. The participants were very satisfied or extremely satisfied after the perception of the DLM result. Conclusion: The study demonstrated that the isolated treatment of MLD for the EGF, obtains satisfactory results, being able to help the professionals in the choice, contributing to the improvement of the women’s self-esteem.